USE OF INFORMATION TECHNOLOGIES IN IMPROVING NUTRITION HYGIENE EDUCATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article discusses the issues of improving nutrition hygiene education based on modern information technologies. It analyzes the possibilities of using digital tools, multimedia resources, electronic textbooks, and interactive platforms in teaching informatics to develop students’ culture of healthy eating and healthy lifestyle habits.